HAKIKAT GAYA BELAJAR AUDIOTORI DALAM PANDANGAN FILSAFAT - Nora Nasution (At-Tazakki: Jurnal Kajian Ilmu Pendidikan Islam dan Humaniora, 2022)
Abstract: Different learning styles have an influence on student learning outcomes. Learning style is a way of reacting and using the stimulants he receives in the learning process. Furthermore, it is said that learning style is a consistent way carried out by students in capturing stimulus or information, how to remember, think and solve problems. This research uses an interpretive paradigm, namely the collection of data from nature (natural setting) as the main / core data through book readings in the study of educational philosophy and learning styles in learning. The data in this study analyzes and increases Learning Motivation what are the supporting factors and obstacles to student Learning Motivation through learning styles and philosophical views. The source of data in this study comes from book documents and expert scientific studies. Then the results are transcribed and classified as needed. The results and discussions show Individuals have a tendency to auditory learning styles are likely to learn better by listening. They enjoy moments of listening to what is conveyed by others. Such a characteristic of learning models really puts hearing as the main tool of absorbing information or knowledge. This means that the first step in learning students must be to hear, only then be able to remember and understand the information received. Keywords: Auditory learning style, philosophical view